Peran Ganda dan Kelelahan Emosional terhadap Komitmen Organisasi dengan Kepuasan Kerja sebagai Variabel Mediasi pada Karyawati CV Nika Indonesia - Khulub Tanwirul; LukLuk Atul Hidayati (Jurnal Maksipreneur, 2012)
This study aims to determine the effect of directly and indirectly influence the effect of the dual role and emotional exhaustion to organizational commitment with job satisfaction as a mediating variable. The data was collected using a total sampling, the respondents as many as 30 people. The analytical method used is path analysis. Results of the study that states there is a direct effect of the dual role to organizational commitment is not evident, while the indirect effect of the dual role to organizational commitment through the mediation of job satisfaction is evident. The direct effect on emotional exhaustion to organizational commitment is not evident and there is an indirect effect of emotional exhaustion to organizational commitment through the mediation of job satisfaction is an evident.